Pengaruh Jenis Pelarut Terhadap Aktivitas Antioksidan Ekstrak Daun Kejompot (Crassocephalum crepidioides) Menggunakan Metode Maserasi - Christinela Domithesa, Maria; Kencana Putra, I Nengah; Sri Wiadnyani, Anak Agung Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2021)
This study aims to determine the effect of various solvent towards antioxidant activity of kejompot (crassocephalum crepioides) extract and to know the right solvent to obtained extract with the highest antioxidant activity. This study used a Completely Randomized Design Method with 4 treatment (water, methanol 70%, ethanol 70%, acetone 70%,) using maseration method. The treatment was repeated four times to obtain 16 experimental units. If there was a significant effect on the observed parameters, then followed by Duncan multipple range test. The result showed that the treatment significantly effected (P<0.05) on each of parameters such as : yield, tanin total, flavonoid, vitamin C, antioxidant activity. This study showed that methanol 70% as the best treatment that obtained yield, tannin, flavonoid, Vitamin C and antioxidant activity respectively 18.76 %, 1.05 mg TAE/g, 7.59 mg QE/g, 8.68 mg AAE/g, and 103.1 ppm antioxidant activity based on IC 50  .